RANCANG BANGUN SISTEM INFORMASI FITNESS CENTER SATRIA GYM SEMARANG BERBASIS WEB (Information Technology and Telematics, 2015)
Abstract                    Satria Gym Fitness Center is one of the gym which is still growing in Semarang. The system is currently running is still using a manual process. So often troublesome admin.                    Therefore created a web-based information system that is easy to apply and can be accessed by anyone. Making this information system using the programming language PHP and MySQL database. The design of the system is done by using DFD. Testing System information Satria Gym Fitness Center done by trying every function on this information system and see the output of each of these functions.                    From designing and testing that has been waged, has produced an information system Satria Gym Fitness Center is capable of doing automation in member registration system, the election schedule, preparing reports and other supporting facilities.  Keywords : Fitness Center, Satria Gym, Web-Based Information System.